KOMPATIBILITAS AJARAN ISLAM DENGAN HAM - Abdul Latief (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2012)
This research discussed the compatibility of Islamic teaching with Human Rights. The issue was how the suitablity between the Islamic Shar’i and Human Rights. In analyzing the problem, the author used Shar’i and anthropological approach to the deductive and inductive method. Basically this study was an elaboration of one of the central themes in Islamic Shar'i namely Human Rights, which currently marginalized from current Islamic thinking developing in society. " Islam " and " Human Rights " are two themes are always controversial, but very rarely have the initiative – creative to explore its suitability . In fact, between Islam and Human Rights, there is a certain point that can connect or reconcile both of them. To determine the suitable point had to start from the history that Islam was derived into the earth as a response to social, economic, political, cultural chaos, and human godless traditions of Ignorance at that time. constructed society into tribes often killed each other, massacred, cheated each other, and so on. In shortly, Islam was revealed to arrange conditions by calling on all people to maintain in each person's social, economic, political , and cultural rights. On the other hand, Human Rights also upheld the right of a person . This is the basic why the author says Islam becomes compatible with human rights. In addition, to find the correspondence point between Islam and Human Rights was a constancy of commitment that Islam is a blessing religion . religion is to educate good thing for human to create peace in this world . This case was relevant between Islamic teaching and Human Rights to correspond as ideas that support human values , in order to realize a fair, prosperous, and peaceful society